Molecular Mechanisms Involved in the Ionic-strength-dependent Stabilization of Actin Filaments - Joanna Gruszczynska-Biegala; Andrzej Stefan; Andrzej A. Kasprzak; Piotr Dobryszycki; Sofia Khaitlina; Hanna Strzelecka-Golaszewska (Current Topics on Chemistry and Biochemistry Vol. 6, 2022)
Formation of stable actin filaments, critically important for actin functions, is determined by the ionic strength of the solution. However, not much is known about the elements of the actin fold involved in ionic-strength-dependent filament stabilization. In this work, F-actin was destabilized by Cu2+ binding to Cys374, and the effects of solvent conditions on the dynamic properties of F-actin were correlated with the involvement of Segment 227-235 in filament stabilization. The results of our work show that the presence of Mg2+ at the high-affinity cation binding site of Cu-modified actin polymerized with MgCl2 strongly enhances the rate of filament subunit exchange and promotes the filament instability. In the presence of 0.1 M KCl, the filament subunit exchange was 2–3-fold lower than that in the MgCl2-polymerized F-actin. This effect correlates with the reduced accessibility of the D-loop and Segment 227-235 on opposite filament strands, consistent with an ionic-strength- dependent conformational change that modulates involvement of Segment 227-235 in stabilization of the intermonomer interface. KCl may restrict the mobility of the \(α\)-helix encompassing part of Segment 227-235 and/or be bound to Asp236 at the boundary of Segment 227-235. These results provide experimental evidence for the involvement of Segment 227-235 in salt-induced stabilization of contacts within the actin filament. This stabilizzation is observed at ionic conditions close to the physiological and weakens by a modification of the C-terminus, which may be of physiological importance because a hydrophobic cleft between subdomains 1 and 3 where the C-terminus is situated is a target for numerous G- and F-actin-binding proteins controlling actin dynamics in the cell.